Global optimization in action continuous and Lipschitz optimization ; algorithms, implementations and applications - Pintér, János D. (Nonconvex optimization and its applications, 1996)
The present volume provides a comprehensive discussion of adaptive partition strategies to solve global optimization problems under very general structural requirements. A unified approach to numerous known algorithms makes possible their straightforward generalizations and extensions, with a view towards efficient computer-based implementations. A considerable part of the book is devoted to various applications, including some generic problems from numerical analysis, and several case studies in environmental systems analysis and management. The book is essentially self-contained, and is based on its author's research, in cooperation (on applications) with a number of colleagues. Audience : The prospective circle of readers includes professors, students, researchers and other professionals from the fields of operations research, management science, industrial and applied mathematics, computer science, engineering, economics and environmental sciences